2018
DOI: 10.3389/fphar.2018.00113
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Synthetic Peptide Corresponding to the ACTH-Like Sequence of Human Immunoglobulin G1 in Experimental Autoimmune Encephalomyelitis

Abstract: Peptide immunocortin sequence corresponds to the amino acid residues 11–20 of the variable part of human immunoglobulin G1 (IgG1) heavy chain. Since immunocortin was shown previously to inhibit phagocytosis in peritoneal macrophages and ConA-induced T-lymphocytes proliferation in culture, we suggested that immunocortin administering may be of use for patients with self-immune syndrome. Immunocortin in concentration 10 μM inhibited proliferation of both antigen (myelin)-induced and ConA-induced LN lymphocytes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Multiple sclerosis (MS) is an autoimmune disease that occurs in central nervous system (CNS). [1] Unfortunately, current therapies of MS are based on non-specific immunosuppressive drugs, such as natalizumab, fingolimod, mitoxantrone, and dimethyl fumarate, which have many side effects. [1,2] The pathogenesis of MS is mediated primarily by T cells that are activated by CNS autoantigens and finally damage the myelin sheath to generate active lesions in the CNS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple sclerosis (MS) is an autoimmune disease that occurs in central nervous system (CNS). [1] Unfortunately, current therapies of MS are based on non-specific immunosuppressive drugs, such as natalizumab, fingolimod, mitoxantrone, and dimethyl fumarate, which have many side effects. [1,2] The pathogenesis of MS is mediated primarily by T cells that are activated by CNS autoantigens and finally damage the myelin sheath to generate active lesions in the CNS.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Unfortunately, current therapies of MS are based on non-specific immunosuppressive drugs, such as natalizumab, fingolimod, mitoxantrone, and dimethyl fumarate, which have many side effects. [1,2] The pathogenesis of MS is mediated primarily by T cells that are activated by CNS autoantigens and finally damage the myelin sheath to generate active lesions in the CNS. [3] Typically, studies of MS and its animal model, experimental autoimmune encephalomyelitis (EAE), have focused on CD4 + T cells, which is induced by myelin antigens (aEAE) or adoptive transfer of myelin-reactive T cells (tEAE).…”
Section: Introductionmentioning
confidence: 99%
“…MCM on MS are non-speci c immunosuppressive drugs, which remains many side effects. [15] Typically, studies of MS and EAE have focused on CD4 + T cells, however, CD8 + T cells are involved in MS/EAE pathogenesis. [16] As we reported previously, myelin oligo-dendrocyte glycoprotein (MOG) 35−55 -speci c CD4 + and CD8 + autoreactive T cells from B6 EAE mouse were encephalitogenic, and our previous data already showed that CD8 + T cells were unique and independent on pathogenic of EAE rather than their CD4 + counterparts.…”
mentioning
confidence: 99%